Hepatitis B e Antigen (HBeAg) Rapid Test and Alanine Aminotransferase Level–Based Algorithm to Identify Pregnant Women at Risk of HBV Mother-to-Child Transmission: The ANRS 12345 TA PROHM Study. (19th March 2020) - Segeral, Olivier; Dim, Bunnet; Durier, Christine; Prak, Sophearot; Chhim, Kearena; Vong, Chanlina; Pech, Sothy; Tiv, Say; Nem, Bunthoeun; Hout, Kay; Nouhin, Janin; Chhun, Samsorphea; et al.
Abstract: Background: The paucity of hepatitis B virus (HBV) DNA measurement in low-/middle-income countries hinders the identification of HBV-infected pregnant women at risk of perinatal transmission. This study evaluates the validity of an algorithm selecting HBeAg-positive women and HBeAg-negative women with alanine aminotransferase (ALT) ≥40 IU/L as a predictor of high HBV DNA level. Methods: All women with reactive samples for hepatitis B surface antigen (HBsAg) were assessed with an SD BIOLINE HBeAg rapid test and HBV DNA quantification was performed. Validities of HBeAg and of the algorithm to identify HBV DNA >2 thresholds (5.3 and 7.3 log10 IU/mL) were evaluated. Results: For the 515 HBsAg-positive women, median age was 29 years, 92 (17.9%) were HBeAg positive, 47 (9.1%) were HBeAg negative with ALT ≥40 IU/L, and 144 (28.0%) had an HBV DNA >5.3 log10 IU/mL. Sensitivity and specificity of HBeAg were 61.8% and 99.2% for HBV DNA >5.3 log10 IU/mL and 81.3% and 96.7% for HBV DNA >7.3 log10 IU/mL. For the algorithm, sensitivity and specificity were 79.2% and 93.3% for HBV DNA level >5.3 log10 IU/mL and 92.7% and 88.1% for HBV DNA >7.3 log10 IU/mL. The AUCs for the algorithm (0.92 and 0.94 for HBV DNA >5.3 and 7.3, respectively) were significantly greater ( P < .001) than the AUCs for HBeAg (0.81 and 0.89 for HBV DNA >5.3 and 7.3, respectively). Conclusions: An algorithm using HBeAg and ALT level could be an effective strategy to identify HBV-infected pregnant women at risk of perinatal transmission in countries where HBV DNA quantification is not routinely available. Abstract : An algorithm selecting Hepatitis B e Antigen (HBeAG)-positive and HBeAg-negative women with ALT ≥40 IU/L could be an effective strategy to identify pregnant women with hepatitis B virus (HBV) eligible for antiviral preventive treatment in countries where HBV DNA quantification is not routinely available.